Sanctuary Earth in Ecological Science Fiction Cinema in the USSR: Per Aspera ad Astra - Zhanna Budenkova (The February Journal, 2023)
This article analyzes the Soviet science-fiction film Per Aspera ad Astra [Cherez ternii k zvezdam, 1980] using the lens of sanctuary. Shot in the period of the Brezhnev Stagnation, shortly before the Chernobyl disaster, the film articulates a range of pressing ecological concerns, but displaces them from Earth and the USSR to the imaginary alien planet Dessa. In her analysis, the author focuses on the paradoxical nature of this displacement and show how the representation of Earth as an unproblematic ecological sanctuary is haunted by its own contradictions. The author also explores how this representational strategy responded to the technoscientific ethos of Soviet modernity that contributed to the destruction of natural environments in the twentieth century.